2015
DOI: 10.1038/nplants.2015.141
|View full text |Cite
|
Sign up to set email alerts
|

Faecal mimicry by seeds ensures dispersal by dung beetles

Abstract: The large brown, round, strongly scented seeds of Ceratocaryum argenteum (Restionaceae) emit many volatiles found to be present in herbivore dung. These seeds attract dung beetles that roll and bury them. As the seeds are hard and offer no reward to the dung beetles, this is a remarkable example of deception in plant seed dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…All cases of S. spretus burial involved limited movement of seeds (<0.25 m) from seed piles, whereas E. flagellatus moved seeds up to 2 m. S. spretus beetles were observed to frantically bury up to three seeds (n=2) and often five or more seeds (n=4) per excavated hole (see the video in the supplementary material online). E. flagellatus was observed to only bury seeds individually, similarly to observations by Midgley et al 1 Flies of the Sarcophagidae were frequently observed to settle on C. argenteum seeds (Figure 1d), indicating that they too are deceived by the scent of the seeds. These 'flesh flies' are typically attracted to dung, carrion or rotting vegetation.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…All cases of S. spretus burial involved limited movement of seeds (<0.25 m) from seed piles, whereas E. flagellatus moved seeds up to 2 m. S. spretus beetles were observed to frantically bury up to three seeds (n=2) and often five or more seeds (n=4) per excavated hole (see the video in the supplementary material online). E. flagellatus was observed to only bury seeds individually, similarly to observations by Midgley et al 1 Flies of the Sarcophagidae were frequently observed to settle on C. argenteum seeds (Figure 1d), indicating that they too are deceived by the scent of the seeds. These 'flesh flies' are typically attracted to dung, carrion or rotting vegetation.…”
Section: Resultssupporting
confidence: 61%
“…Chemically the seeds have characteristics of the dung of both of the most common large herbivores in the reserve: the eland (Taurotragus oryx) and the bontebok (Damaliscus pygargus pygargus). 1 However, the seeds are more similar in shape and size to the smaller faeces of the bontebok, which is then the possible visual model that C. argenteum mimics. At the same Potberg site, during February 2016, we observed similar seed dispersal of C. argenteum seeds by another dung beetle, Scarabaeus spretus zur Strassen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALs are large in both species, suggesting that, in general, dung beetles strongly rely on olfactory cues for many behaviors, such as finding a specific type of dung, animal, or plant (Mansourian et al, 2016;Midgley, White, Johnson, & Bronner, 2015) or for being attracted to pheromones of the male specimen (Burger, 2014;Tride & Burger, 2011). In the two species investigated here, the difference in activity period does not substantially affect the number of AL glomeruli (about 83 in the diurnal species; about 86 in the nocturnal species).…”
Section: Comparison Between Diurnal and Nocturnal Dung Beetlesmentioning
confidence: 77%
“…Losey & Vaughan, ; Nichols et al , ; Beynon et al , ); germination and/or secondary dispersal of seeds owing to dung relocation by beetles (e.g. D'hondt et al , ; Santos‐Heredia et al , ; Midgley et al , ); dung beetle behaviour associated with provisioning/relocation of food for the larvae (e.g. Halffter & Edmonds, ; Klemperer, ; Dacke, ; Dacke et al , ); dung preferences (e.g.…”
Section: Introductionmentioning
confidence: 99%